PEMANFAATAN LAHAN PEKARANGAN SEBAGAI UPAYA PEMENUHAN KEBUTUHAN KELUARGA DI DESA KANJILO KECAMATAN BAROMBONG KABUPATEN GOWA - Amruddin Amruddin; Muhammad Iqbal (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2018)
This study aims to find out how the use of yard land so far, and how the population in the utilization of yard in the village Kanjilo Barombong District Gowa regency. Population taking in this research is all population that have land yard in Kanjilo Village amounted to 202 people, sample in penenlitian is done by simple random sampling by taking sample as much as 15% from population amount, so that obtained 30 respondents as sample in this research. Data analysis used in this research is descriptive analysis by using scoring analysis. The results showed that the utilization of yard area in Kanjilo Village, Barombong District, Gowa Regency, was categorized as good with range 66,7 and interval 33,3, so have opportunity to continue to be maintained and maintained by utilizing yard land in effort to fulfill family need. which is used in the utilization of the yard is very easy, planting media and planting materials are easily obtained. Utilized yard land with various types of vegetable crops, toga, and spices that can meet the needs of families in everyday and financial gain for the people of the Village Kanjilo Barombong District Gowa District.